Correlations between preclinical BJAB assay ranking of antisense drugs and clinical trial adverse events - Wesley Partridge; Sebastien A. Burel; Annie Ferng; Shuting Xia; T. Jesse Kwoh; Scott P. Henry; Brenda F. Baker (Wiley, 2023)
Abstract This analysis sought to assess the clinical predictivity of an in vitro assay which utilized the human B‐lymphoma BJAB cell line, for identification of antisense oligonucleotides (ASOs) with the potential to elicit innate immune activation in humans. Adverse events (AEs) from clinical trial data were analyzed based on prior clinical knowledge and network analysis of the clinical data to identify correlations with the BJAB assay. Clinically evaluated ASOs were ranked by the BJAB assay's mean log‐fold increase in TNF expression levels. Flu‐like reactions (FLRs) and injection site reactions (ISRs), were chosen as AEs of interest, along with those Medical Dictionary for Regulatory Activities preferred terms identified using AE network analysis. Fifteen different 2'‐O‐methoxyethyl (2'MOE) modified ASOs were ranked by the incidence of each AE group in the integrated safety data from 35 clinical trials. ISRs are considered to be local to the injection site, whereas FLRs are reflected by systemic constitutional symptoms. The correlations identified in this analysis of integrated clinical data provide evidence that the ASO sequences selected by the BJAB assay have a lower likelihood of causing systemic inflammatory AEs associated with FLRs, but not ISRs.